2021
DOI: 10.1101/2021.06.26.450044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural dynamics of stroboscopic stimulation at different stimulation frequencies

Abstract: Stroboscopic stimulation has been previously shown to induce visual hallucinations and altered states of consciousness, state by entraining the brain to the driving frequency, similar to those reported during the psychedelics although little systematic research exists on the effect of specific stimulation frequency on experience. The present study investigated the effects of different stroboscopic stimulation frequencies on neural dynamics, such as signal diversity (Lempel-Ziv complexity) and spectral power an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In recent years, there has been increasing interest in using AVS specifically to passively induce desired mood states. AVS is also integral to a new wave of so-called "technodelics" 5,6 or "cyberdelics" 7 designed to enhance one's mind and wellbeing, often by inducing a psychedelic-adjacent experience in a nonpharmacological fashion by producing visual perceptions of complex geometric patterns (i.e., form constants; Figure 1B) akin to the hallucinogenic effects of LSD or psilocybin [8][9][10][11][12] . Empirical research into the neural mechanisms of AVS has demonstrated neuromodulatory effects such as alteration of EEG frequencies or complexity 9,10,13 , neural entrainment [14][15][16] , or neuroplastic changes 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been increasing interest in using AVS specifically to passively induce desired mood states. AVS is also integral to a new wave of so-called "technodelics" 5,6 or "cyberdelics" 7 designed to enhance one's mind and wellbeing, often by inducing a psychedelic-adjacent experience in a nonpharmacological fashion by producing visual perceptions of complex geometric patterns (i.e., form constants; Figure 1B) akin to the hallucinogenic effects of LSD or psilocybin [8][9][10][11][12] . Empirical research into the neural mechanisms of AVS has demonstrated neuromodulatory effects such as alteration of EEG frequencies or complexity 9,10,13 , neural entrainment [14][15][16] , or neuroplastic changes 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…AVS is also integral to a new wave of so-called "technodelics" 5,6 or "cyberdelics" 7 designed to enhance one's mind and wellbeing, often by inducing a psychedelicadjacent experience in a nonpharmacological fashion by producing visual perceptions of complex geometric patterns (i.e., form constants; Fig. 1B) akin to the hallucinogenic effects of LSD or psilocybin [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%